“NOMA” GENRE AND ITS FORMATION AS A GENRE IN UZBEK CLASSIC LITERATURE - Temurova Iroda Inom qizi, (TADQIQOTLAR, 2026)
Abstract: The article describes epistolary genre and its development as genre in Uzbek classical literature. The works of the nomadic genre from the end of the XIV century and the first half of the XV century are listed. Moreover, the life of their time, the aspirations of the people, the glorification of patriotism, justice and equality, love and devotion and other issues of these epistolary works have been analyzed.